Pemberdayaan Masyarakat Melalui Home Industry Pindang Tongkol Di Desa Tambaksari Kecamatan Rowosari Kabupaten Kendal - Nilam Sari, Dewi; Riyadi, Agus (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Background: In Tambaksari Village, apart from being famous for its fisheries sector, it also has other potential, namely in the plantation sector. Examples are bananas, papaya, breadfruit, and so on. Then also in the field of animal husbandry (ducks, cows, goats), as well as in the field of culture (Nyadran, dance). Of these various potentials, the most prominent is in the fisheries sector, so in this case it can be exploited by the pindang tuna home industry business. The purpose of this service is to find out more about the important role of the home industry of tuna fish farming carried out by the Tambaksari Village community in efforts to empower the community through utilizing the local potential of the local area. Method: Methods and techniques used in implementing the community empowerment program through the Pindang Tongkol home industry in Tambaksari Village, Rowosari District, Kendal Regency. Before carrying out this service activity, the proposer held an FGD (Focus Group Discussion) meeting with stakeholders and potential service partners with the agenda of equalizing perceptions about planned activities to be implemented. Result: The home industry has a very important role in development in economic growth. In relation to empowerment efforts through this home industry business, an owner acts as a facilitator who facilitates the local community to learn about how to process pindang tuna fish which has high selling power. Conclusion: The role of home industry businesses is as a development role in economic growth.